Nuclear techniques applied to provenance and technological studies of Renaissance majolica roundels from portuguese museums attributed to della Robbia Italian workshop - Dias, M. I. (2017)
Fundação para a Ciência e a Tecnologia support through the UID/Multi/04349/2013 and PTDC/HIS/HEC/116742/2010 projects; H2020 CHARISMA funded (Grant Agreement no. 228330) project at Budapest Neutron Center; FB, MNAA, MNAz, FCG, MJ for sampling and field measurements.